Development of new synthetic methods towards prins cyclization - Liu, Feng (2010)
A brief introduction to major aspects of Prins cyclization is presented in Chapter 1. Two strategies were attempted via exploitation of the steric and electronic effects in Chapter 2, and a novel and efficient trans Prins cyclization reaction was disclosed by exploiting the electronic effect or the neighboring participation effect. In Chapter 3 & 4, a Friedel-Crafts-Prins cascade reaction was developed to construct polycyclic THP/DHP and furans rings from propargylic and allylic epoxides in an efficient and diastereoselective manner. In Chapter 5, suppression of oxonia-Cope rearrangement was achieved by tuning the reaction conditions and substrates, leading to the development of a novel cis Prins cyclization reaction of allenic alcohols. By far, the application of this methodology to the synthesis of (+)-Sambutoxin was unsuccessful due to the low reactivity of the starting pyridinone aldehyde.